ANALISIS YURIDIS DAMPAK GLOBALISASI TERHADAP INVESTASI PADA SEKTOR IT DI INDONESIA - Pretama, I Wayan Gde; Cokorde Istri Dian Laksmi Dewi; Kadek Ary Purnama Dewi (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Investment plays a crucial role in driving economic growth and stability, especially for developing countries like Indonesia. Amid the rapid currents of globalization and digitalization, the information technology (IT) sector has emerged as a strategic area with great potential to attract investment and strengthen national competitiveness. Globalization has accelerated the transformation of the IT sector through technological advancements such as cloud computing, artificial intelligence, and the Internet of Things, fundamentally reshaping the global economic landscape. However, alongside these opportunities lie complex legal challenges, including data privacy protection, intellectual property rights, and legal certainty for foreign investors. Investment regulations—particularly the roles of the Investment Coordinating Board (BKPM) and the Online Single Submission (OSS) system—serve as key instruments in fostering a conducive investment climate in Indonesia. This study aims to provide an in-depth analysis of the impact of globalization on investment in the IT sector from a legal perspective, and to evaluate the extent to which Indonesia’s national legal system can accommodate these global dynamics. Using a descriptive-analytical approach, this research is expected to offer a comprehensive overview of the legal and regulatory challenges faced, as well as strategic recommendations to enhance legal protection and certainty for investors in Indonesia’s information technology sector.